2020
DOI: 10.3389/fphar.2020.00861
|View full text |Cite|
|
Sign up to set email alerts
|

Shikonin Inhibits Cancer Through P21 Upregulation and Apoptosis Induction

Abstract: Shikonin is a natural naphthoquinone compound and has demonstrated potent anticancer activities; however, the underlying molecular mechanisms remained elusive. Here we report that Shikonin inhibited the growth of a wide range of human cancer cell lines, illustrating a broad anticancer effect. Mechanistically, we show that Shikonin arrested the cell cycle at the G2/M phase, inhibited the ERK-dependent cell growth signal, and induced cell death in both P53 wild type and mutant cancer cells, which collectively co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 53 publications
(64 reference statements)
2
28
0
Order By: Relevance
“…Growth and proliferation inhibition after treatment with SHI was associated with a cell cycle arrest of parental PC3 and DX-resistant DU145 cells in the G2/M phase, and an S-phase arrest in DX-resistant 22Rv1. Furthermore, in pancreatic, lung [ 25 ], breast [ 31 ], gastric cancer cells [ 26 ], and melanoma [ 49 ] the administration of SHI resulted in cell cycle arrest in the G2/M phase. In a study on therapy-sensitive PC3 and DU145 cells, SHI induced a shift to the G2/M phase [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Growth and proliferation inhibition after treatment with SHI was associated with a cell cycle arrest of parental PC3 and DX-resistant DU145 cells in the G2/M phase, and an S-phase arrest in DX-resistant 22Rv1. Furthermore, in pancreatic, lung [ 25 ], breast [ 31 ], gastric cancer cells [ 26 ], and melanoma [ 49 ] the administration of SHI resulted in cell cycle arrest in the G2/M phase. In a study on therapy-sensitive PC3 and DU145 cells, SHI induced a shift to the G2/M phase [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is isolated from the dried roots of Lithospermum erythrorhizon . Several studies show that SHI, in addition to its function as a color pigment, has antimicrobial [ 22 ], antiinflammatory [ 23 ], and antitumor [ 24 , 25 ] activity.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have reported that Shikonin has antitumor effect, which is mainly related to cycle, apoptosis, autophagy, necrosis and immune escape. The molecules and signaling pathways involved include Bcl-2, p53 [21], cIAP1/2 [22], P21 [23], PD-L1 [24], HIF1α/PKM2 [25], PI3K/ AKT /mTOR [26], MAPK [27], NF-κB/STAT3 [24] and so on. Compared with the previous reports, our study focused on the effect of Shikonin on glycolysis, which was consistent with the study of Zhao et al [8].…”
Section: Discussionmentioning
confidence: 99%
“…Shikonin has already demonstrated a broad spectrum of pharmacological properties that show significant potential for therapeutic development ( Zhang et al, 2018b ). Specifically, shikonin exhibits significant pharmacological activities both in vitro and in vivo , including anti-inflammatory, anti-fungal, and anti-HIV effects ( Wang et al, 2020c ). Jin et al recently reported that shikonin can effectively inhibit the replication of SARS-CoV-2 M pro r in vitro with an EC 50 at 15.75 μM ( Jin et al, 2020 ).…”
Section: Promising Active Ingredients Of Chinese Herbal Medicine Thatmentioning
confidence: 99%